A comparative study of the factors affecting the growth/development of the rural community newspaper the Zoutpansberger and Mirror, Northern Province - Lubinga, Elizabeth Nviri (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2001.